Food Restriction-Induced Changes in Gonadotropin-Inhibiting Hormone Cells are Associated with Changes in Sexual Motivation and Food Hoarding, but not Sexual Performance and Food Intake - Klingerman, Candice M.; Williams III, Wilbur P.; Prasad, Ankita; Brahme, Nina; Simberlund, Jessica; Schneider, Jill E.; Kriegsfeld, Lance J. (Frontiers in Endocrinology, 2011)
We hypothesized that putative anorectic and orexigenic peptides control the motivation to engage in either ingestive or sex behaviors, and these peptides function to optimize reproductive success in environments where energy fluctuates. Here, the putative orexigenic peptide, gonadotropin-inhibiting hormone (GnIH, also known as RFamide-related peptide-3), and the putative anorectic hormones leptin, insulin, and estradiol were examined during the course of food restriction. Groups of female Syrian hamsters were restricted to 75% of their ad libitum food intake or fed ad libitum for 4, 8, or 12 days. Two other groups were food-restricted for 12 days and then re-fed ad libitum for 4 or 8 days. After testing for sex and ingestive behavior, blood was sampled and assayed for peripheral hormones. Brains were immunohistochemically double-labeled for GnIH and the protein product of the immediate early gene, c-fos, a marker of cellular activation. Food hoarding, the number of double-labeled cells, and the percent of GnIH-Ir cells labeled with Fos-Ir were significantly increased at 8 and 12 days after the start of food restriction. Vaginal scent marking and GnIH-Ir cell number significantly decreased after the same duration of restriction. Food hoarding, but not food intake, was significantly positively correlated with cellular activation in GnIH-Ir cells. Vaginal scent marking was significantly negatively correlated with cellular activation in GnIH-Ir cells. There were no significant effects of food restriction on plasma insulin, leptin, estradiol, or progesterone concentrations. In the dorsomedial hypothalamus (DMH) of energetically challenged females, strong projections from NPY-Ir cells were found in close apposition to GnIH-Ir cells. Together these results are consistent with the idea that metabolic signals influence sexual and ingestive motivation via NPY fibers that project to GnIH cells in the DMH.